New species of Polystomoides (Monogenoidea: Polystomatidae) parasitizing the urinary bladder of a freshwater turtle in Brazil - Lignon, Julia Somavilla; Cohen, Simone Chinicz; Justo, Marcia Cristina Nascimento; Du Preez, Louis; Comarella, Carine Glaucia; Nishimaru, Rogerio Akio; Souza, Paulo Vinicius Abbade Moreira [UNESP]; de Ataíde, Michelli Westphal; Müller, Daniel Curvellho de Mendonça; Brun, Maurício Veloso; Monteiro, Silvia Gonzalez (FapUNIFESP (SciELO), 2023)
Trachemys dorbigni is the most abundant freshwater turtle species in Rio Grande do Sul, southern Brazil. Chelonians are known to host a wide variety of pathogens, including viruses, bacteria, hemoparasites and helminths. Among these, nine genera of polystomatid flatworms (Monogenoidea; Polystomatidae) infect freshwater turtles: Apaloneotrema, Aussietrema, Fornixtrema, Manotrema, Pleurodirotrema, Polystomoidella, Polystomoides, Uropolystomoides and Uteropolystomoides. However, little is known about the biology of these parasites in the Neotropical Realm. Through investigative cystoscopy, specimens of Polystomatidae were located inside the urinary bladder of the host T. dorbigni. Retrieved specimens were fixed and stained whole mounts prepared for taxonomic identification. In the present paper, a new species of Polystomoides (Monogenoidea: Polystomatidae) parasitizing the urinary bladder of a freshwater turtle of the species T. dorbigni in Brazil is described. Polystomoides santamariensis n. sp. differs from the congeneric species on the length of the genital spines, which are longer. Given the enormous diversity of freshwater turtles around the world, it is likely that a large number of chelonian polystomatids are still unknown.
Nova espécie de Polystomoides (Monogenoidea: Polystomatidae) parasitando a bexiga urinária de uma tartaruga de água doce no Brasil
Keywords: chelonians; Platyhelminthes; Rio Grande do Sul; Trachemys dorbigni